2021
DOI: 10.3390/sci3040045
|View full text |Cite
|
Sign up to set email alerts
|

Replacement Strategies for Animal Studies in Inhalation Testing

Abstract: Animal testing is mandatory in drug testing and is the gold standard for toxicity and efficacy evaluations. This situation is expected to change in the future as the 3Rs principle, which stands for the replacement, reduction, and refinement of the use of animals in science, is reinforced by many countries. On the other hand, technologies for alternatives to animal testing have increased. The need to develop and use alternatives depends on the complexity of the research topic and also on the extent to which the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 106 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…A main feature in modeling respiratory epithelium using cell culture is the necessity for the air-liquid interface at the apical side of the monolayer. Hence, cells are grown on a membrane with the medium on one side of the membrane, i.e., the basolateral side, and the apical side exposed to air, often with oxygen concentrations [ 40 ]. This setup will facilitate polarized differentiation of the cells, formation of intercellular junctions, and expression of native proteins, including metabolizing enzymes [ 41 ].…”
Section: In Vitro Dissolution and Permeability Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A main feature in modeling respiratory epithelium using cell culture is the necessity for the air-liquid interface at the apical side of the monolayer. Hence, cells are grown on a membrane with the medium on one side of the membrane, i.e., the basolateral side, and the apical side exposed to air, often with oxygen concentrations [ 40 ]. This setup will facilitate polarized differentiation of the cells, formation of intercellular junctions, and expression of native proteins, including metabolizing enzymes [ 41 ].…”
Section: In Vitro Dissolution and Permeability Testing Methodsmentioning
confidence: 99%
“…Examples of tissue models that, according to their suppliers, have the barrier function and potential phenotype for drug delivery experiments are those developed commercially by Epithelix (MucilAir™ and SmallAir™) and MatTek 3D (EpiAirway™, EpiAirway-FT™, and EpiAlveolar™). A wider application of these can be seen in the literature for toxicity studies, while the applicability for drug delivery research is being investigated [ 40 ]. Furthermore, the authors of the current review article recommend referring to a recent review article published by Eedara et al (2022) where more examples of the absorption of orally inhaled drugs can be found [ 55 ].…”
Section: In Vitro Dissolution and Permeability Testing Methodsmentioning
confidence: 99%
“…Respiratory diseases are globally among the most common diseases, especially chronic obstructive pulmonary disease (COPD) and asthma ( 2 ). COPD and asthma together with cystic fibrosis (CF) have been identified as the third leading cause of death worldwide ( 4 , 5 ). Acute respiratory infections can induce pneumonia, either through community- or hospital-acquired pathogens or through inflammation induced by prolonged mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…cystic fibrosis (CF) have been identified as the third leading cause of death worldwide (4,5). Acute respiratory infections can induce pneumonia, either through community-or hospital-acquired pathogens or through inflammation induced by prolonged mechanical ventilation.…”
mentioning
confidence: 99%
“…It is therefore crucial, in accordance with the reinforcement of the 3Rs (replace, refine, and reuse), rule, to favor alternative NHP aerosol models [ 16 ] before experimentation on living NHPs, such as macaques. One attractive possibility is to use an in vitro replica of the NHP respiratory system.…”
Section: Introductionmentioning
confidence: 99%